Evaluasi kinerja struktur baja dengan ikatan angin terhadap beban gempa pada proyek ester plant - Rudi Rahwidianto; Hermansyah (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2026)
Indonesia is a region located at the confluence of active tectonic plates so it has a high level of earthquake risk. This condition requires buildings, especially steel structures in multi-storey industrial buildings, to have good resistance to earthquake loads. One of the efforts to improve the rigidity and stability of the structure is to use a type X wind bonding system (bracing). The analysis was carried out on two models, namely structures without wind bonds and structures with type X wind bonds. This study aims to evaluate and compare the performance of steel structures without wind bonding and with type X wind bond to earthquake load in the Ester Plant Project building in Medan City. The results of the analysis showed that the structure without wind bond had a natural vibration period of 1,776 seconds, while the structure with type X wind bond had a natural vibration period of 1,434 seconds. The addition of type X wind bonds increases the rigidity of the structure so that it is able to reduce the natural vibration period and produce a better structural response to earthquake loads. The use of type X wind bonds has been proven to improve the performance of steel structures against earthquake loads by increasing the rigidity of the structure and lowering the period of natural vibration. Thus, the type X wind bonding system is feasible to be applied as an alternative to improve the durability of steel structures in high-rise industrial buildings.